2019
DOI: 10.1111/ocr.12329
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in the gingival crevicular fluid used to detect root resorption in patients undergoing orthodontic treatment: A systematic review

Abstract: Objectives To evaluate whether changes in the concentration of different biomarkers in the gingival crevicular fluid (GCF) can be used to detect the root resorption process in adult or adolescent patients undergoing treatment with a fixed appliance, in comparison with untreated subjects or treated patients not showing signs of root resorption. Material and Methods The following databases were analysed in the period between June 2017 and March 2018, without any language and initial date restrictions: PubMed, EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In orthodontics, clinicians claimed to get an ideal result with optimum force magnitude and minimum adverse effect with lower time of treatment. Many researchers have therefore studied the profile and the levels of various enzymes, cytokines, growth factors and proteoglycans, primarily in the oral fluids (GCF and saliva), in order to monitor orthodontic tooth movement with its subsequent reactions in humans without any invasive impact 2,17 .…”
Section: Discussionmentioning
confidence: 99%
“…In orthodontics, clinicians claimed to get an ideal result with optimum force magnitude and minimum adverse effect with lower time of treatment. Many researchers have therefore studied the profile and the levels of various enzymes, cytokines, growth factors and proteoglycans, primarily in the oral fluids (GCF and saliva), in order to monitor orthodontic tooth movement with its subsequent reactions in humans without any invasive impact 2,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Results of a systematic review by Tarallo et al [ 20 ] compared different biomarkers in the GCF to detect root resorption in patients undergoing orthodontic treatment. They concluded that DPP was the most specific biomarker for early diagnosis of root resorption and suggested it to be used in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, previous studies suggested that the most indicative markers for the diagnosis of root resorption were dentin specific proteins only. Proteins like dentin sialoprotein have been suggested to be less indicative, since they were found to be present in both the root cement matrix and the dentin [ 20 , 21 ]. Consequently, dentin phosphoprotein was selected as the biomarker for this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, limited studies have investigated the OPN level in the GCF of the healthy control, which was lower compared to those who had periodontitis [25]. The later groups had the highest OPN expression beside a positive correlation with the clinical attachment loss and pocket depth in pre-periodontal treatment [26].…”
Section: Groupsmentioning
confidence: 96%